Effects of RANKL-Targeted Therapy in Immunity and Cancer - Cheng, Michael L.; Fong, Lawrence (Frontiers in Oncology, 2014)
The role of the RANKL/RANK system is well characterized within bone, where RANKL/RANK signaling mediates osteoclastogenesis and bone resorption. However, this system has also been shown to influence biologic processes beyond the skeletal system, including in the immune system and in cancer. RANKL/RANK signaling is important in lymph node development, lymphocyte differentiation, dendritic cell survival, T-cell activation, and tolerance induction. The RANKL/RANK axis may also have direct, osteoclast-independent effects on tumor cells. Indeed, activity of the RANKL/RANK pathway in cancer cells has been correlated with tumor progression and advanced disease. Denosumab, a fully human monoclonal antibody against RANKL, inhibits osteoclastogenesis and is widely used not just for the treatment of osteoporosis, but for the prevention of skeletal-related events from bone metastases in solid malignancies such as breast and prostate cancer. The potential effects of denosumab on the immune system have been largely ignored. Nevertheless, with the emergence of immunotherapies for cancer, denosumab may impact the effectiveness of these therapies, especially if they are given in combination. In this article, we review the role of RANKL/RANK in bone, immunity, and cancer. Examining the potential effects of routine treatment with denosumab beyond the bone represents an important area of investigation.